Terapi Alternatif dalam Mengatasi Depresi Postpartum melalui Cognitive Behavior Therapy (CBT): Tinjauan Narasi - Suzanna Suzanna; Nova Mardiana; Kgs Muhammad Faizal (Universitas Malahayati Lampung, 2023)
ABSTRACT Every year the number of people with postpartum depression is increasing in the world. There are several therapies that are effective in reducing postpartum depression, one of which is cognitive behavioral therapy. Cognitive Behavioral Therapy is one of the most widely applied psychotherapy approaches and has been shown to be effective in treating a variety of disorders, including anxiety and depression. To review the relationship with the effect of cognitive behavioral therapy on postpartum depression. The search for articles was carried out using electronic databases such as Google Scholar, PubMed and Science Direct to answer writing purposes. The combination of keywords used in the article search was postpartum depression, cognitive behavior, behavior therapy, cognitive behavior therapy. From 10 research articles that havee been conducted, it is shown that all cognitive behaavior therapy are effective in reducing postpartum depression. This literature review shows the effect of cognitive behavioral therapy on postpartum depression. Increase the role of nurses in recognizing mood disorders after delivery so that they can be prevented before they get worse. Keywords: Postpartum Depression, Cognitive Behavior Therapy ABSTRAK Setiap tahun angka penderita depresi postpartum semakin meningkat di dunia. Ada beberapa terapi yang efektif dalam menurunkan depresi postpartum salah satunya yaitu Cognitive Behavior Therapy. Cognitive Behavior Therapy merupakan salah satu pendekatan psikoterapi yang paling banyak diterapkan dan telah terbukti efektif dalam mengatasi berbagai gangguan, termasuk kecemasan dan depresi. Untuk mereview literature yang berhubungan dengan pengaruh Cognitive Behavior Therapy terhadap depresi postpartum. Pencarian artikel dilakukan dengan menggunakan database elektronik Pubmed, Science Direct, Proquest dan Google Scholar untuk menjawab tujuan penulisan. Kombinasi kata kunci yang digunakan dalam pencarian artikel adalah postpartum depression dan cognitive behavior therapy. Dari 10 artikel penelitian yang telah dilakukan menunjukkan bahwa semua terapi Cognitive Behavior Therapy efektif dalam menurunkan depresi postpartum. Literature review ini menunjukkan adanya pengaruh Cognitive Behavior Therapy terhadap depresi postpartum. Meningkatkan peran perawat dalam mengenali adanya gangguan mood setelah melahirkan sehingga dapat di cegah sebelum lebih parah. Kata Kunci : Depresi Postpartum, Terapi Perilaku Kognitif